If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -2x + 12 = -5x + 7x Reorder the terms: 12 + x + -2x = -5x + 7x Combine like terms: x + -2x = -1x 12 + -1x = -5x + 7x Combine like terms: -5x + 7x = 2x 12 + -1x = 2x Solving 12 + -1x = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 12 + -1x + -2x = 2x + -2x Combine like terms: -1x + -2x = -3x 12 + -3x = 2x + -2x Combine like terms: 2x + -2x = 0 12 + -3x = 0 Add '-12' to each side of the equation. 12 + -12 + -3x = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -3x = 0 + -12 -3x = 0 + -12 Combine like terms: 0 + -12 = -12 -3x = -12 Divide each side by '-3'. x = 4 Simplifying x = 4
| 2x-4=3x+7-2x | | 5a+6-2a=12 | | 0,2(x+1)-0,4(x+3)+0,6(x+5)=0,8 | | 3-2x=2(4x+12) | | 2/5c+4-2.3=7.6 | | 9-(2x+1)*3-4(x+5)=-4 | | 2(x+4)+5=17 | | 7(x+2)-6(x-3)=24 | | 4-5(x+11)=20+2(3-4x) | | 131+155x=155 | | 131+150x=150 | | 131+.21x=x | | 50=1.8c+32 | | 3(x+8)+2=9x+8 | | 131+.24x=x | | 22=.5b(8) | | 2/3a^2=13 | | 3w+10=35 | | 4x^2-36x^2=0 | | 2/5+3/4-1/2= | | 2w+5(4)=60 | | 36x^2-y^2= | | -0.1417x^2+23.365x=946.12 | | 5+.25=13 | | 3x^2-4=503 | | 3(x-1)*(x-1)+4x-4=0 | | 3(x-1)+4x-4=0 | | 17-x=2x+5 | | e=g+p/2 | | 3x+7-x=11 | | 15=2x+3x+5 | | x-5-2x=9 |